Absolute spectral backscatter measurements of large-core multimode PMMA polymer optical fibers - Dengler, Simon A.; Engelbrecht, Rainer; Schmauß, Bernhard (Optics Express, 2021)
To our knowledge, we are the first to measure the absolute value of the backscattering coefficient of a standard 1 mm core-diameter, multimode (MM) step-index (SI) polymethylmethacrylate (PMMA) polymer optical fiber (POF) for the spectral range of 450 nm to 700 nm. Our optical time domain reflectometer (OTDR) setup consists of a femtosecond supercontinuum laser with an acousto-optical filter as a tunable light source with short pulses and a time-correlated single-photon counting system as a receiver with a high dynamic range. The backscattering coefficient is calculated from the ratio between the energy within the fiber end reflex and the distributed backscattering level. We also measured the spectral attenuation with our OTDR setup and compared it with a standardized measurement method. At the attenuation minima within the measured spectral range the backscattering level of a 1 ns pulse is about -46 dB at 520 nm, -48 dB at 570 nm, and -51 dB at 650 nm. We were also able to show by the observed wavelength dependence that Rayleigh scattering causes a majority of the scattering.
CRIS-Team Scopus Importer:2021-10-22